Estudo da redução fotocatalítica e fotoeletrocatalítica de 'CO IND. 2' em meio aquoso sobre 'CU'/'CU IND. 2 'O'', 'TI' 'O IND. 2'/'PT', 'CU''NB' 'O IND. 3' - 'CU''O' e 'CU IND. 0,85''ZN IND. 0,15''NB IND. 2''O IND.6' como catalisadores para formação de metanol - Brito, Juliana Ferreira de [UNESP] (2014)
This present work reports the main results obtained with the construction and characterization of TiO2 nanotubes modified by platinum nanoparticle electrode (TiO2/Pt) and copper covered by copper oxide nanoparticles electrode (Cu/Cu2O) for application in the photoelectrocatalytic reduction of dissolved CO2 and CuNbO3-CuO, Cu0,85Zn0,15Nb2O6 and ZnNb2O6-Nb2O5 powders semiconductors constructed and applied in the photocatalytic reduction of dissolved CO2 for the generation of products with higher added value. The TiO2/Pt and Cu/Cu2O electrodes were prepared by electrochemical techniques, whereas the CuNbO3-CuO, Cu0,85Zn0,15Nb2O6 and ZnNb2O6-Nb2O5 powder semiconductors were prepared using the combustion synthesis technique and submitted to annealed. The CO2 reduction by photoelectrocatalysis and photocatalysis were not satisfactory when using the TiO2/Pt electrode and the ZnNb2O6-Nb2O5 semiconductor, respectively. However, the Cu/Cu2O electrode shows a high efficiency in the CO2 reduction obtaining 80% of removal in 0.3 mol L-1 Na2CO3 pH 9 and +0.2 V, and, it showed a practically selective reaction to methanol (producing 5.63 mmol L-1), corresponding to 20% of conversion at ambient of 0.1 mol L-1 NaHCO3/Na2CO3 butter solution pH 8, using UV light of 125 W and +0,2 V. The CuNbO3-CuO and Cu0,85Zn0,15Nb2O6 powder semiconductors also showed a good efficiency to the methanol formation throughout dissolved CO2 reduction in 0.1 mol L-1 Na2CO3 pH 8 using visible light of 450 W, and forming 7 mmol L-1 and 3.2 mmol L-1 of methanol, respectively. The results obtained in this work show that both techniques can be employed for the CO2 reduction, using for this the Cu/Cu2O, CuNbO3-CuO and Cu0,85Zn0,15Nb2O6 semiconductors, and it could be a potential alternative to the environmental problems and contribute as raw material source for the production of fuels, for instance.